Xanton dari Fraksi Aktif Antioksidan Kulit Batang Kandis Gajah (Garcinia griffithii T. Anders) - Elfita Elfita; Supriyatna Supriyatna; Huesin H Bahti (Fakultas Biologi | Universitas Jenderal Soedirman, 2007)
Garcinia is a large genus of polygamous trees or shrubs, distributed in the tropical Asia, Africa, and Polynesia, and is a rich source of bioactive molecules including xanthones, flavonoids, benzophenones, lactones, and phenolic acid. In the present study, an attempt was made to evaluate the antioxidant activity from stem bark of G. griffithii using radical scavenging 1,1-diphenyl-2-picryl hydrazyl (DPPH) model systems. Xanthone from antioxidant active fraction had been isolated and this compound had been identified by the use of ultraviolet (UV), infrared (IR), and proton nuclear magnetic resonance (1H-NMR) spectroscopy.